Job Description Kejelasan Tanggung Jawab dan Aplikasinya Persfektif Hadist Nabi Muhammad SAW - Ramli L; Ambo Asse; Muhammad Yahya (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to find out the job description, clarity of responsibilities and application from the perspective of the hadith of the Prophet Muhammad SAW. Data is obtained from articles published through Google Scholar. Initially, the search was carried out using relevant keywords such as